Sinonasal sarcoidosis: a case report - Erdoğan Düzcü, Selma; Köybaşı Şanal, Serap (The European Research Journal, 2020)
Sarcoidosis is an idiopathic and multisystemic chronic disease characterized by non-caseating granulomas. Sinonasal sarcoidosis may be seen in an isolated form or related to a multisystemic disease. A 48-year-old female patient visited the otolaryngology department with complaints of headache and nasal obstruction for two years. The physical examination revealed a saddling on the nose, and crusted fragile mucosa was observed bilaterally in nasal endoscopy. Paranasal CT showed invasion of the right orbita. In chest X-ray, there was bilateral hilar enlargement, and lung biopsy revealed non-caseating granulomas. A bilateral endoscopic sinus surgery was applied to the patient. Upon histopathological demonstration of multiple non-caseating granulomas in the specimen, the diagnosis of sinonasal sarcoidosis was made. The patient responded well to the following steroid treatment. Although rare, sarcoidosis should be taken into consideration in differential diagnosis of sinonasal diseases.